Cardiovalve in mitral valve position—Additional solution for valve replacement - Sherif, Mohammad; Sündermann, Simon H.; Maisano, Francesco; Pieske-Kraigher, Elisabeth; Riess, Juliane; Reinthaler, Markus; Mai, Gunther; Trippel, Tobias Daniel (Frontiers in Cardiovascular Medicine, 2022)
We report on a 72 yrs old male patient with recurrent heart failure hospitalizations caused by severe mitral regurgitation due to severe restriction of the posterior mitral leaflet treated with the transfemoral mitral valve replacement (TMVR) system Cardiovalve. Immediate interventional success was obtained resulting in a quick mobilization and discharge.